PENGARUH RELAKSASI MEDITASI BENSON TERHADAP PEMENUHAN KEBUTUHAN TIDUR LANSIA DI BALAI SOSIAL LANJUT USIA MANDALIKA MATARAM - Mas’adah Mas’adah (STIKes Adi Husada, 2018)
ABSTRACT Sleep disturbances such as insomnia generally occur in elderly that occurs due to various factors namely physical, environmental, and psychological factors. One of the physical factors suffered by the elderly is rheumatic pain and complaints caused by this disease often leads to the fulfillment of elderly sleep needs to decline. The purpose of this study explains the effect of relaxation of benson meditation on the fulfillment of elderly sleep needs. The design of this research is experimental quasy with one group pretest posttest design. The population is all elderly rheumatic pain sufferers in Mandalika Seni Mandalika Hall. The sample in the study amounted to 26 elderly. The independent variables of this study are relaxation of benson meditation and dependent variable of elderly sleep requirement. Data were taken through open and closed interview using PSQI instrument then analyzed using Wilcoxon Sign Rank Test. The result of the ststistic test shows that p = 0,000 means p <0.05. Benson meditation relaxation techniques affect the thought process that is forwarded to the hypothalamus which later produces Corticotropin Releasing Hormon Factor (CRF) causes the body to relax and create feelings of pleasure so that the needs of sleep will be fulfilled. Relaxation of benson meditation has an effect on the fulfillment of elderly sleep requirement at Balai Sosial Mandalika. Keywords : relaxation of benson meditation, PSQI, fulfillment of elderly sleep needs